2022
DOI: 10.3390/cimb44020052
|View full text |Cite
|
Sign up to set email alerts
|

Single Circulating-Tumor-Cell-Targeted Sequencing to Identify Somatic Variants in Liquid Biopsies in Non-Small-Cell Lung Cancer Patients

Abstract: Non-small-cell lung cancer (NSCLC) accounts for most cancer-related deaths worldwide. Liquid biopsy by a blood draw to detect circulating tumor cells (CTCs) is a tool for molecular profiling of cancer using single-cell and next-generation sequencing (NGS) technologies. The aim of the study was to identify somatic variants in single CTCs isolated from NSCLC patients by targeted NGS. Thirty-one subjects (20 NSCLC patients, 11 smokers without cancer) were enrolled for blood draws (7.5 mL). CTCs were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Several studies have utilized the AccuCyte-CyteFinder platform to detect CTCs in various cancers such as prostate, breast, and lung ( 9 , 10 , 26 , 28 , 29 , 31 33 ). This study is the first to examine CTCs using this platform in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have utilized the AccuCyte-CyteFinder platform to detect CTCs in various cancers such as prostate, breast, and lung ( 9 , 10 , 26 , 28 , 29 , 31 33 ). This study is the first to examine CTCs using this platform in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the platform has a single-cell retrieval device, CellPicker™, where identified cells can be picked for single-cell molecular characterization. This includes genomic analysis such as TP53 mutations in breast cancer cells ( 27 ), APC mutations in colorectal cancer ( 36 ), targeted mutational panels in prostate ( 31 ) and lung cancer ( 33 ); and single-cell RNA sequencing as demonstrated in breast cancer ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC patients with overexpression of PTCH1 displayed a better outcome ( Herreros-Pomares et al, 2022 ). Moreover, PTCH1 expression was found to be correlated with NSCLC development ( Barbirou et al, 2022 ). One circulating tumor cell NGS assay in early-stage lung cancer patients showed that more than 50% of lung cancer patients presented four common mutations, including Notch1, EGFR, IGF2, and PTCH1 ( Wan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 24 chapters present the contributions of 166 researchers from 16 countries: Brazil (14), China (12), Ecuador (2), Greece (10), Hungary (8), Italy (4), Japan (25), Korea (29), Mexico (11), Poland (5), Portugal (2), Russia (2), Switzerland (7), the UK (1) and the USA (27). The articles reported new molecular findings regarding the following types of cancer: blood [ 1 , 2 ], breast [ 3 , 4 , 5 ], kidney [ 6 ], liver [ 7 , 8 ], lung [ 9 , 10 , 11 , 12 ], ovary [ 10 , 13 , 14 ], prostate [ 15 ], soft tissue [ 16 ], gastric [ 17 , 18 ], testicular [ 19 ], cervical [ 20 , 21 ], and adrenal gland [ 22 ].…”
mentioning
confidence: 99%
“…For instance, Armakolas et al [ 8 ] compared the proteome profiles, expression of selected miRNAs and abundance of circulating tumor cells among a group of 56 people with advanced and 33 people with early hepatocellular carcinoma, 28 with cirrhosis and 5 healthy controls. Barbirou et al sequenced circulating tumor cells to identify somatic variants in people with non-small-cell lung cancer [ 9 ]. An interesting study by Bel’skaya et al [ 5 ] compared the saliva “omic” characteristics of 487 females with breast cancer with those of 298 healthy controls.…”
mentioning
confidence: 99%